Trust in Government and Compliance With Stay at Home Orders in American States - Oguzhan C. Dincer (Center for Economic Studies and Ifo Institute (CESifo), 2021)
Trust in government is particularly important in implementing public health policies especially during crises such as the COVID-19 pandemic. This study investigates the effects of trust in government and compliance with stay at home orders using data from American states during the first wave of the pandemic. A system of four seemingly unrelated regression (SUR) equations covering four consecutive Saturdays starting with April 25 is estimated with maximum likelihood. The regression results indicate that people are more likely to comply with stay at home orders in more trusting states.
Keywords: I18; D70; D73; 330; trust in government; Covid-19; social distancing